Heart and Head: Profiles and Predictors of Self-Assessed Cognitive and Affective Empathy in a Sample of Medical and Health Professional Students - Giusti, Laura; Mammarella, Silvia; Salza, Anna; Ussorio, Donatella; Bianco, Denise; Casacchia, Massimo; Roncone, Rita (Frontiers in Psychology, 2021)
For medical and health professions, students learning to respond to others' distress with well-regulated empathy is an important developmental skill linked to positive health outcomes and professionalism. Our study aimed to investigate the sociodemographic, psychological, and psychosocial differences between medical (MS) and health professional (HPS) students and their empathic abilities, since both populations share common stressors, namely, dealing with suffering people. Additionally, we were interested in assessing the psychological and psychosocial predictors of empathy of MS compared to HPS. One hundred thirty MS and eighty-six HPS were administered the Patient Health Questionnaire-9, Interpersonal Reactivity Index, Integrative Hope Scale, and UCLA Loneliness Scale. The two groups showed differences in their contextual characteristics, with the HPS group having larger families, lower parents’ education levels, and lower family income compared to the MS group. In both groups, approximately 15% of students reported previous contact for psychological problems. A higher proportion of HPS (23.3%) reported depressive symptoms than MS (10%), and female HPS reported more intense feelings of loneliness than other subgroups of students. No differences were found between the two groups in self-assessed cognitive and affective empathy. In both groups, women showed greater affective scores than men and, at the same time, seemed to be particularly prone to personal distress. The cognitive empathic dimension of “perspective taking” was predicted by young age (OR, 612; 95% CI, 1.395-15.242) and the overall socioeconomic status (OR, 3.175; 95% CI, 1.154-8.734) of the HPS. Self-assessed affective competence was predicted by female gender (OR, 3.112; 95% CI, 1.328-7.288), depressive symptomatology (OR, 2.777; 95% CI, 1.004-7.681), higher mother’s level of education (OR, 2.764; 95% CI, 1.147-6.659), and feeling of hope related to social relationships (OR, 1.367; 95% CI, 1.152-1.622). Risk factors for poor self-assessed affective emphatic skills were previous contact for psychological problems (OR, 3.263; 95% CI, 1.238-8.601) and feelings of loneliness (OR, 1.18; 95% CI, 1.09-1.276). Our findings emphasize the need to test psychosocial models to better understand empathic skills